PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PRESTASI BELAJAR BAHASA INDONESIA PADA SISWA KELAS IV UPT SDN 2 TURATEA KABUPATEN JENEPONTO - Muh. Aswardi; Sukri Syamsuri, Andi; Agus, M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the implementation of the jigsaw cooperative learning model on the Indonesian language learning achievement of fourth-grade students at UPT SDN 2 Turatea, Jeneponto Regency. This study is a pre-experimental study with a one-group pretest–posttest design. The subjects were all 20 fourth-grade students, with a total sampling technique. Data collection techniques were carried out through written tests, observations, and documentation. The instruments used were learning outcome tests and student activity observation sheets. Data analysis techniques included descriptive statistical analysis and inferential statistics through normality tests, homogeneity tests, and paired sample t-tests. The results showed that the average pretest score of 54.65 was in the low and incomplete category, while the average posttest score increased to 85.75 in the high and complete category. The results of the hypothesis test showed a significance value of <0.05 so that H₀ was rejected and H₁ was accepted. Thus, it can be concluded that the application of the jigsaw type cooperative learning model has a significant effect on the Indonesian language learning achievement of fourth grade students at UPT SDN 2 Turatea, Jeneponto Regency.